Effects of Multisession High-Definition Transcranial Direct Current Stimulation on Resting-State Brain Network Connectivity and Efficiency Under Running-Induced Fatigue - Changxiao Yu; Jianglong Zhan; Bin Shen; Junhong Zhou; Weijie Fu (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
This study aimed to investigate the effects of five-session high-definition transcranial direct current stimulation (HD-tDCS) on resting-state brain network connectivity and efficiency under running-induced fatigue. This double-masked, randomized, and sham-controlled study involved 24 male adults randomly assigned to the HD-tDCS or sham-tDCS group. Participants completed a running-induced fatigue protocol at a personalized running speed before and after the intervention, and heart rate (HR) and Borg rating of perceived exertion (RPE) were monitored. Resting-state electroencephalography (EEG) signals from 28 channels were recorded before the intervention and after fatigue was induced. Brain network connectivity was characterized using average functional connectivity measured using the phase locking value, and network efficiency was assessed using graph theoretical indices. Compared with the sham-tDCS group, the HD-tDCS group showed significantly increased averaged functional connectivity ( ${p} =0.019$ ), clustering coefficient ( ${p} =0.036$ ), and local efficiency ( ${p} =0.020$ ) in the theta band, and the global efficiency ( ${p} =0.020$ ) in the gamma band relative to the baseline values. The $Δ $ HR ( ${p} \lt 0.001$ ) and $Δ $ RPE values ( ${p} =0.019$ ) significantly decreased in the HD-tDCS group relative to sham-tDCS group and baseline values. Multiple sessions of anodal HD-tDCS targeting the primary motor cortex can enhance resting-state brain network connectivity and efficiency in the theta and gamma bands under running-induced fatigue, and reduce the perceived effort during running.